Android-Based Shortest Path Finding Using A-Star (A*) Algorithm in Bekasi City - Herlawati Herlawati; Prima Dina Atika; Ajif Yunizar Pratama Yusuf; Fata Nidaul Khasanah; Endang Retnoningsih; Beno Aditya Sanusi; Gedhe Hilman Wakhid (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2021)
Getting information on routes can be he main problem for visitors. For example in determining the route to a proper place for eating and how to find the closest route to a mall. Based on the existing problems, this study proposes an application for finding information about places that visitors want to go based on the closest route. Algorithm A-Star (A*) was implemented that uses the distance estimation by finding the closest path to the destination using a heuristic function as a basis to select from several alternatives effectively. The result showed that an android application can give the information about the location of places to visit for eating and malls by calculating the distance from the starting point to the end point.